Reproduction and brooding of Crepidula argentina, Simone, Pastorino & Penchaszadeh 2000 (Gastropoda: Calyptraeidae) - Cledón, Maximiliano (2001)
Crepidula argentina is a protandric hermaphrodite that undergoes complete sex change. Males develop a mature gonad when the shell length is 4 mm. Sex change begíns when shell length is around 8 mm and continues until 11 mm, when the first pre-vitellogenic oocytes are found. The minimum and maximum shelllengths for a brooding female are respectively 15 and 36 mm. There is a well-defined seasonal reproductive cycle; females brood between August and April. Females brood between 10 and 46 (mean 25) egg capsules per egg mass. The intracapsular Huid is translucent and viscous in recently laíd capsules but becomes less dense closer to hatching. Neither nurse eggs nor cannibalism have been observed. The mean number of eggs per mass was 5600 ± 3300. The egg capsules have a mean width of 2.1 mm (SD = 0.03 mm, = 52), and a mean length of 2.4 mm (SD = 0.04 mm, = 52). Each egg capsule contains about 320 embryos. The uncleaved egg diameter is about 170 u.m. All eggs develop synchronously in the same brood. The embryos hatch as planktotrophic veligers with a shell length of 190-230 um and a bilobed velum about 160 u.m in width. The mean size of the egg capsules, number of embryos per egg capsule, and number of embryos per brood are positively correlated wíth female shell length.